2021
DOI: 10.1111/hex.13262
|View full text |Cite
|
Sign up to set email alerts
|

Priorities and preferences for care of people with multiple chronic conditions

Abstract: Background To guide the development of high‐quality care for people with multiple chronic conditions, partners of the European Joint Action CHRODIS developed the Integrated Multimorbidity Care Model. To assess its suitability for improving care for people with multimorbidity in the Netherlands, the model was piloted in a primary care setting with both patients and care providers. Aim This paper reports on the patient perspective, and aims to explore the priorities, underlying values and preferences for care of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Due to the multidimensional nature of multimorbidity, it is of great relevance that the healthcare provided is holistic and that the clinical pathway is not only based on single diagnoses. People with multimorbidity, that is, two or more diagnoses [24], need person-centred care (PCC), a model in which HCPs need to develop a certain skill mix [25]. In Western countries, there is a growing acknowledgement that quality health services should be effective, safe and person-centred, as well as timely, equitable, integrated and efficient [26].…”
Section: Person-centred Integrated Carementioning
confidence: 99%
“…Due to the multidimensional nature of multimorbidity, it is of great relevance that the healthcare provided is holistic and that the clinical pathway is not only based on single diagnoses. People with multimorbidity, that is, two or more diagnoses [24], need person-centred care (PCC), a model in which HCPs need to develop a certain skill mix [25]. In Western countries, there is a growing acknowledgement that quality health services should be effective, safe and person-centred, as well as timely, equitable, integrated and efficient [26].…”
Section: Person-centred Integrated Carementioning
confidence: 99%
“…This effect was absent in participants in vaccination centers. The results might be explained by a generally higher GP consultation rate in patients with chronic conditions and, therefore, a stronger familiarity with their GP and the procedures in the practice [30]. Further, we found in both sites that with increasing age the preference for a SARS-CoV-2 vaccination administered by a GP increased, indicating that older people favored either to be vaccinated in a familiar setting [19] or shorter travel distances [17].…”
Section: Participants' Socio-demographic Characteristics and Their In...mentioning
confidence: 72%
“…The perspectives of people with multimorbidity have been documented in earlier work, including the need for a holistic approach to care, continuity of care and establishing trusting relationships with care professionals. 18 , 19 Other sources have identified delays in appointments and referrals experienced by people with multimorbidity, which can be a significant factor influencing care outcomes. 19 Further, studies have found that those with multimorbidity ‘reported better coordination of care when they had more time with their General Practitioner, which ultimately improved individualised care’.…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity presents complex care challenges requiring a comprehensive systems-wide approach to better address both clinical and non-clinical care needs 10 , 17 . This requires strategic and operational change to care systems based on collaborative care models that deliver the holistic and person-centred care necessary to improve care outcomes for this cohort 18 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%